127 - EVALUATION OF GROWTH IN CHILDREN WITH SIX MONTHS OF LIFE IN THE URBAN AREA OF CITY OF ARCOVERDE-PE/BRAZIL (Fiep Bulletin - online, 2011)
Growth is a dynamic and continuous process of life, expressed by the increase in body size and is one of the best indicators of child health. The research aimed to evaluate the growth of 44 children with six months of life, seen in fifteen Programs of Family Health in the Urban Area of Arcoverde-PE/Brazil. The anthropometric variables were analyzed: ae, weight (kg), height (cm), head circumference (cm), weight/height, weight/age, height/age, as well as socioeconomic variables of families. Statistically, the descriptive analysis, the Spearman's rank Correlation (rho) and the t Test of Student were used. The results indicated a correlation between the length and weight, which means that the kids had linear growth during the period studied. The children grew within normal limits in the relations: weight/age, height/age and head circumference, however, the relation weight/height did not meet these criteria; and there were significant differences between groups in the behavior of the weight. It is concluded that programs for pregnant women and children, aged six months, has been effective, as the family participates together the multidisciplinary healthcare team, not being seen, therefore, patterns of abnormality in the anthropometric variables studied.
Keywords: growth; anthropometry; children